Sensory Profiles in School-Age Children with Developmental Language Disorder. Issue 3 (4th May 2022) - Simpson, Kate; Paynter, Jessica; Ziegenfusz, Shaun; Westerveld, Marleen
ABSTRACT: There has been limited research on identifying and understanding co-occurring challenges associated with Developmental Language Disorder (DLD). This is an exploratory study to examine the sensory profile of school-age children with DLD, and to investigate possible relationships between sensory profiles and language skills. Chart information was extracted for 28 children ( M age = 6 years 11 months) who attended a language specialist school in Australia. The children's sensory profile was compared with normed data, and associations between sensory and language skills were investigated. Probable or definite difference to sensory stimuli was reported on 60% of the children. There was no correlation between sensory responses and language skills. Identifying and understanding the relationship of co-occurring features associated with DLD aids in future development of interventions to better support children with DLD.